The Effect of Perceived Quality, Customer Satisfaction, Corporate Image, Customer Experience on Customer Loyalty - Missy Salim; Rodhiah Rodhiah (Budapest International Research and Critics University, 2022)
The purpose of this study was to examine the effect of perceived quality, customer satisfaction, corporate image and customer experience on customer loyalty. The population of this study are users of the LINE Webtoon application in Jakarta. This study uses a sample with a non-probability method. The sample selection technique is purposive sampling. The number of samples is 100 respondents who use the LINE Webtoon application. The data collection technique used a questionnaire distributed online via google form. The analysis technique uses SEM which is then processed with smartPLS. The results of this study indicate that perceived quality and customer experience have a positive and significant effect on customer loyalty. However, customer satisfaction and company image have no significant effect on customer loyalty.